2012
DOI: 10.1007/s00221-012-3298-y
|View full text |Cite
|
Sign up to set email alerts
|

The brain uses efference copy information to optimise spatial memory

Abstract: Does a motor response to a target improve the subsequent recall of the target position or can we simply use peripheral position information to guide an accurate response? We suggest that a motor plan of the hand can be enhanced with actual motor and efference copy feedback (GoGo trials), which is absent in the passive observation of a stimulus (NoGo trials). To investigate this effect during eye and hand coordination movements, we presented stimuli in two formats (memory guided or visually guided) under three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It allows us to perform complex and precise operations, correct for errors, and quickly adapt to unexpected changes in our environment [1][2]. These processes can be fairly complex since the representation of most of our actions and goals comprises several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…It allows us to perform complex and precise operations, correct for errors, and quickly adapt to unexpected changes in our environment [1][2]. These processes can be fairly complex since the representation of most of our actions and goals comprises several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of vocal pitch regulation, errors heard in auditory feedback may be detected by comparing the auditory re-afference with a sensory memory trace of the vocal target, with perceived discrepancies eliciting a corrective motor command to regulate the vocal production 23 . Working memory functions to integrate incoming information with stored information in existing memory 24 , and it has been suggested that information related to the speech motor command and sensory re-afference can be stored in short-term memory within a feedback circuit and recalled when needed to adjust the motor activity 25 26 . On the other hand, activation of the brain’s error detection system is affected by characteristics of the working memory system 27 , and the error detection mechanisms can benefit from training of working memory, as evidenced by increased amplitudes of the error-related negativity (ERN) using electroencephalography (EEG) for participants who received a training of auditory, visual, and cross-modality working memory skills using the CogniFit Personal Coach Program 28 .…”
mentioning
confidence: 99%
“…Accurate reaching may also arise from proprioceptive eye signals (Enright 1995;Gonzalez and Burke 2013;Henriques et al 2002;Lazzari et al 1997;Ren et al 2006). In our experiment, reaches were made in a dark room, but we did not explicitly remove visual feedback of hand position during the reach.…”
Section: Discussionmentioning
confidence: 99%